Aeroacustic and Vibroacoustic Advancement in Aerospace and Automotive Systems - Roberto Citarella (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The purpose of this special issue is to highlight the latest advances in vibroacoustics and aeroacoustics applied to aerospace and automotive industries. In proposing this wide topic, we wanted to give scientists and engineers the opportunity to publish their studies of current interest, both in the theoretical and experimental fields of vibration, sound generation, and radiation; and passive and active noise control approaches, which can be of interest for assessing vibroacoustics characteristics of aerospace and automotive vehicles. In particular, we have tried to include articles focusing on the introduction of new approaches and methodologies in the vibroacoustics and aeroacoustics fields.